2020
DOI: 10.1371/journal.pone.0236339
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of commonly used predictive scoring systems in Indigenous Australians with sepsis: An observational study

Abstract: Background Indigenous Australians suffer a disproportionate burden of sepsis, however, the performance of scoring systems that predict mortality in Indigenous patients with critical illness is incompletely defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Approximately 17% of the local population identifies as an Aboriginal and/or Torres Strait Islander Australian [ 11 ]. Many members of these Indigenous communities experience significant socioeconomic disadvantage and, accordingly, a high burden of comorbidities, increasing their susceptibility to infection, including CNS disease [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 17% of the local population identifies as an Aboriginal and/or Torres Strait Islander Australian [ 11 ]. Many members of these Indigenous communities experience significant socioeconomic disadvantage and, accordingly, a high burden of comorbidities, increasing their susceptibility to infection, including CNS disease [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these risk factors—markers of greater socioeconomic disadvantage—were more common in the Indigenous patients in this series and might be responsible for their over-representation in this cohort. Indeed, smoking and hazardous alcohol make a significant contribution to the disproportionate burden of communicable and non-communicable diseases in the local Indigenous population and are an obvious target for more aggressive preventative health strategies in the region [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Waikato study found that Māori patients are three times more likely to develop sepsis and are at increased risk of hospital death 9 . Variation in health outcomes according to ethnicity is not unique to NZ; Indigenous Australians are more likely to die from sepsis at a younger age, 33 and in the USA, African American and Hispanic patients have higher rates of sepsis and are more likely to be admitted to ICU 34 . It is therefore prudent that this increased risk for ethnic minority populations is accounted for in ED management strategies in order to provide equitable care.…”
Section: Discussionmentioning
confidence: 99%